Resistance to Fusarium Head Blight, Kernel Damage, and Concentration of Fusarium Mycotoxins in Grain of Winter Triticale (x Triticosecale Wittmack) Lines - Tomasz Góral; Halina Wiśniewska; Piotr Ochodzki; Adriana Twardawska; Dorota Walentyn-Góral (Agronomy, 2020)
Fusarium head blight (FHB) can cause contamination of cereal grain with mycotoxins. Triticale is also infected with FHB; however, it is more resistant than wheat to head infection. The aim of this study was to identify triticale lines that combine low head infection with low toxin contamination. Resistance to FHB of 15 winter triticale and three winter wheat lines was evaluated over a three-year experiment established in two locations. At the anthesis stage, heads were inoculated with Fusarium culmorum isolates. The FHB index was scored and the percentage of Fusarium-damaged kernels (FDKs) assessed. The grain was analysed for type B trichothecenes (deoxynivalenol and derivatives, nivalenol) and zearalenone content. The average FHB index was 10.7%. The proportion of FDK was 18.1% (weight) and 21.6% (number). An average content of deoxynivalenol amounted to 7.258 mg/kg and nivalenol to 5.267 mg/kg. In total, it was 12.788 mg/kg of type B trichothecenes. The zearalenone content in the grain was 0.805 mg/kg. Relationships between FHB index, FDK, and mycotoxin contents were statistically significant for triticale lines; however, they were stronger for FDK versus mycotoxins. Triticale lines combing all types of FHB resistance were found, however the most resistant ones were less resistant that wheat lines with the Fhb1 gene.